On the Cheeger sets in strips and non-convex domains - Leonardi, Gian Paolo; Pratelli, Aldo (Calculus of Variations and Partial Differential Equations, 2016)
In this paper we consider the Cheeger problem for non-convex domains, with a particular interest in the case of planar strips, which have been extensively studied in recent years. Our main results are an estimate on the Cheeger constant of strips, which is stronger than the previous one known from Krejčiřík and Pratelli (Pac J Math 254(2):309–333, 2011), and the proof that strips share with convex domains a number of crucial properties with respect to the Cheeger problem. Moreover, we present several counterexamples showing that the same properties are not valid for generic non-convex domains.
Keywords: Cheeger sets; Isoperimetric; Prescribed mean curvature